Analisis Faktor-Faktor yang Mempengaruhi Korupsi pada Pemerintah Daerah di Jawa Tengah Menggunakan Teori Fraud Triangle - Gilang Satryo Wicaksono; Tri Jatmiko Wahyu Prabowo (Owner : Riset dan Jurnal Akuntansi, 2022)
Cases of corruption that occur are increasing in Indonesia from year to year, including in local government. Various efforts have been made to prevent corruption, but there are still many cases of corruption in local governments in Central Java. The fraud triangle theory is used to find out the causes of corruption, which consist of pressure, opportunity, and rationalization. This study aims to analyze the factors causing corruption in local governments in Central Java using the fraud triangle theory which is proxied using the variables of regional financial performance, regional income, regional capital expenditures, internal audit capabilities, audit opinions, and regional personnel expenditures. This study uses quantitative methods and purposive sampling method using secondary data. The sample in this study is the district/city level local government in Central Java Province for the 2015 – 2019 period, which has a corruption case and has been decided by a first-level court, has been audited by the BPK, has an APIP Capability assessment, and has complete LKPD. The method of data analysis in this study used SPSS with logistic regression method. The results of this study indicate that regional financial performance, regional income, and internal audit capabilities have no effect on corruption, regional capital expenditures and regional personnel expenditures have a significant positive effect on corruption, and audit opinion has a significant negative effect on corruption.